2016
DOI: 10.1596/1813-9450-7529
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Preschool Quality in Promoting Child Development: Evidence from Rural Indonesia

Abstract: This article examines the relationship between preschool quality and children's early development in a sample of over 7,900 children enrolled in 578 preschools in rural Indonesia. Quality was measured by: (1) classroom observations using the Early Childhood Environment Rating Scale-Revised (ECERS-R), (2) teacher characteristics, and (3) structural characteristics of preschools. Children's development was measured using the Early Development Instrument (EDI). The article proposes two methodological improvements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The World Bank (2016) argues that increasing FLFP is a more effective policy than attracting in-migrants or increasing elderly work participation to offset the shrinking workforce due to the rapidly aging economy. In this paper, we also elude to the welldocumented long-term benefits of early childhood education that tend to favor children born in poor households (Berlinski et al 2009, Havnes and Mogstad 2015, Garcia et al 2016Brinkman et. al.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The World Bank (2016) argues that increasing FLFP is a more effective policy than attracting in-migrants or increasing elderly work participation to offset the shrinking workforce due to the rapidly aging economy. In this paper, we also elude to the welldocumented long-term benefits of early childhood education that tend to favor children born in poor households (Berlinski et al 2009, Havnes and Mogstad 2015, Garcia et al 2016Brinkman et. al.…”
Section: Resultsmentioning
confidence: 92%
“…Government regulation stipulates that a preschool should have at most 20 students per teacher. In reality, however, the age-groupings are often ignored, and quality varies across regions and facilities (Brinkman et al 2017).…”
Section: Preschools In Indonesiamentioning
confidence: 99%
“…24 Likewise, the quality of the preschools likely ebbed and flowed during the period under study. Brinkman et al (2017a) establish the strong link between child development outcomes and the quality of the services being provided, as measured using classroom observation. Emerging evidence on how centers evolved during the life of the project and once project funding ended suggests that quality was not static (Hasan et al, forthcoming).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to align the ECERS-R data with the reality of the Indonesian context, we compared ECERS-R to Indonesia's national standard and found that 28 out of 43 ECERS-R items were discussed in the national standard (see Table 4 in Brinkman et al 2017). We, therefore, calculate playgroup quality using only the 28 items that were found to be common between ECERS-R and the national standard.…”
Section: Methodsmentioning
confidence: 99%
“…As noted in Brinkman et al (2017), the project playgroups operated three times a week for 3 hours a day and allowed children between the ages of 3 and 6 to enroll. Project documents suggest that the cost per child was about US$27 per year.…”
Section: Indonesia Early Childhood Education Projectmentioning
confidence: 99%